Virtual Education in Pediatric Surgery during the COVID-19 Era: Facing and Overcoming Current Challenges - Aubert, Ophelia; Wagner, Richard; Gerardo, Rodrigo; Tamaro, Gaia; Zani, Augusto; Ponsky, Todd; Lacher, Martin (European Journal of Pediatric Surgery, 2021)
The novel coronavirus disease 2019 (COVID-19) pandemic has impacted our way of living in an unprecedented manner. Medical professionals at all levels have been forced to adapt to the novel virus. The delivery of surgical services and the subsequent learning opportunities for surgical residents have especially been disrupted and the pediatric surgical community has not been exempted by this. This article highlights the challenges imposed by the pandemic and outlines the various learning modalities that can be implemented to ensure continued learning opportunities throughout the pandemic and beyond. Furthermore, it aims to show how the utilization and expansion of technologies maintain and further increase the communication, as well as the exchange of and access to knowledge among peers. Virtual education-, application-, and simulation-based learning and social media, as well as telemedicine and online conferences, will play a considerable role in the future of surgical specialties and surgical education.
Keywords: virtual teaching; pediatric surgery; COVID-19 pandemic; application; simulation